Bantuan Komputer dan Pelatihan Program Microsoft Word Bagi Guru dan Murid Madrasah Ibtidaiyah Muhammadiyah di Sukoharjo Dan Boyolali - Nugroho, Muhammad Siam Priyono; Setyowati, Suryaning; Sudjatmiko, Aliem; Fadlilah, Umi (Universitas Muhammadiyah Surakarta, 2010)
These community service activities program is a complete infrastructure ofteaching and learning activities like computer device, gives additional knowledgeand skills for teachers and students in computer field and use of simple applicationprograms so they can complete task or job use computer facilities and be motivatedto always follow the developments and advances in information technology, andencourage other parties to participate to provide assistance for other physical facilities. The problem faced by Islamic Elementary School Muhammadiyah and Islamic Elementary School Sraten Al Islam 2 Ngesrep Ngemplak Boyolali (Madrasah Ibtidaiyah Muhammadiyah Sraten and Madrasah Ibtidaiyah Al Islam 2 Ngesrep Ngemplak Boyolali ) is the absence of computers as a learning tool so that needs help and assistance are in the form of some form of computer training. Because of the availability of a number of computers that are not used in the Department of Architecture, Digital Architecture Laboratory FT-UMS and the availability of skilled human resource in the field of computers and training programs, so community service activities be held is in the form of computer assistance and training to Islamic Elementary School (Madrasah Ibtidaiyah ) teachers and students. Results of the Community Service activity is the availability of facilities or learning tool are in the form of computers and knowledge from training activities so its help teachers and students to know, study simple application program, and continue to develop skills independently through these facilities.